1992
DOI: 10.1093/fampra/9.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Encounter and Diagnosed Health Problems: Convergence Between Doctors and Patients

Abstract: This study of 521 encounters in 25 urban general practices in Australia, compares both patient and doctor reported reasons for encounter (RFE) and diagnoses. Although doctors and their patients generally agreed on the overall distribution of RFE and diagnoses that arose, there was disagreement in at least 30% of paired comparisons within individual encounters. There was better agreement for RFE than for diagnoses. This may have been partly due to differences in the classification systems used. However, it sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 0 publications
1
18
1
Order By: Relevance
“…For other subjects related to the consultation agreements ranging from 17% to 100% have been demonstrated (4,5,(10)(11)(12)(13)(14)(15)(16)(17). In our study agreement about all of the four topics examined was observed for only 35% of consultations.…”
Section: Discussioncontrasting
confidence: 43%
“…For other subjects related to the consultation agreements ranging from 17% to 100% have been demonstrated (4,5,(10)(11)(12)(13)(14)(15)(16)(17). In our study agreement about all of the four topics examined was observed for only 35% of consultations.…”
Section: Discussioncontrasting
confidence: 43%
“…Responses are recorded by the GP, about the patient, in discussion with the patient. Using a qualified medical practitioner to record morbidity in conjunction with the patient self-report may provide a more accurate classification of patients’ health problems than the self-report alone 16 17. A total of five SAND subsamples were used: three data collection periods were between January and October 2007; and two between January and March 2010.…”
Section: Methodsmentioning
confidence: 99%
“…4,11,12 Patients are less likely to return for visits when there is a lack of physician-patient concordance, 13 although the relationship is inconsistent. 14,15 Trust is said to be essential to the medical consultation and is related to continuity and patient satisfaction. 16,17 The ability of the physician to enable the patient toward effective self-care is a marker of consultation quality.…”
Section: Physician-patient Relationship and Medication Compliancementioning
confidence: 99%